Quantification of BK Virus Standards by Quantitative Real-Time PCR and Droplet Digital PCR Is Confounded by Multiple Virus Populations in the WHO BKV International Standard. (6th January 2020) - Bateman, Allen C; Greninger, Alexander L; Atienza, Ederlyn E; Limaye, Ajit P; Jerome, Keith R; Cook, Linda
Abstract: BACKGROUND: The WHO recently released a BK virus (BKV) international standard. This study evaluated the WHO international standard and commercially available BKV standards by quantitative real-time PCR (qPCR) and droplet digital PCR (ddPCR). METHODS: WHO, Exact Diagnostics, Acrometrix, and Zeptometrix BKV standards were tested by qPCR and ddPCR. Two preparations of NIST BKV clones were also tested. Nucleic acid was extracted with the Roche MP96 and MPLC, followed by quantification in duplicate. To resolve discrepancies, we sequenced the WHO and NIST materials. RESULTS: Manufacturers' expected copies/mL were close to WHO IU/mL: linear regression of qPCR data revealed 1.12 Exact copies/IU, 0.76 Acrometrix copies/IU, and 0.70 Zeptometrix copies/IU. For ddPCR, similar concentrations were measured when either the VP1 region or the T region was targeted, and concentrations were almost 2-fold higher when both regions were targeted simultaneously. ddPCR results for the VP1 and T regions were similar for all commercial standards, but targeting the T region of the WHO standard led to a 4-fold lower result than the VP1 region. Next-generation sequencing revealed no primer or probe mismatches. However, large differences in coverage across the WHO standard and junctional reads were observed, indicating subpopulations of the WHO standard with deletions in the T region. CONCLUSIONS: BKV standards showed concordance among providers, but the WHO standard contains subpopulations of viruses with various deletions in the T region. PCR results will vary depending on which region of the WHO standard is targeted.